2010
DOI: 10.1203/pdr.0b013e3181bf594b
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem-Cell Transplantation for Hypoxic-Ischemic Brain Injury in Neonatal Rat Model

Abstract: Neonatal hypoxic-ischemic brain injury (HIE) remains a major cause of neurologic disabilities. However, many experimental therapies have shown limited successes. We assessed whether human mesenchymal stem cells (MSCs) could be transplanted in the HIE rat brain to improve neurologic disabilities. P7 SD rats were either subjected to left carotid artery ligation and hypoxic exposure [hypoxia-ischemia (HI)] or sham operation and normoxic exposure (sham). On P10, rat pubs received either PKH26-labeled MSCs or buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 23 publications
(25 reference statements)
2
84
0
6
Order By: Relevance
“…Several experimental studies in neonatal models have shown that treatment with MSCs after ischemic brain injury has beneficial effects on functional outcome (26)(27)(28)(29). Lateralizing motor deficits are decreased by 40-70% after treatment with MSCs, although a decrease in lesion volume is not always reported (26)(27)(28)(29).…”
Section: Msc Transplantationmentioning
confidence: 99%
See 3 more Smart Citations
“…Several experimental studies in neonatal models have shown that treatment with MSCs after ischemic brain injury has beneficial effects on functional outcome (26)(27)(28)(29). Lateralizing motor deficits are decreased by 40-70% after treatment with MSCs, although a decrease in lesion volume is not always reported (26)(27)(28)(29).…”
Section: Msc Transplantationmentioning
confidence: 99%
“…Intracranial injection of MSCs after neonatal ischemic brain injury in rodents improved functional recovery and reduced lesion size (27)(28)(29). Moreover, MSCs transplanted via the intravenous or intracardiac route also improved functional recovery (26,30). To circumvent the invasive procedure of local intracranial administration and the loss of cells after peripheral administration, we studied the possibility of using the intranasal administration route (31).…”
Section: Msc Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, differentiation has mainly been limited to GFAP þ astrocytes. [101][102][103] The inefficiency to undergo in vivo differentiation has also been observed following delivery of NSCs in the injured postnatal neocortex in animal models of HIE. Lee et al 104 reported that the majority of the donor cells remained undifferentiated or became astroglia, with only about 5% and 4% differentiation into neurons and oligodendrocytes, respectively.…”
Section: Animal Models Of Other Sct For Hiementioning
confidence: 99%